2004
DOI: 10.1007/s10038-003-0113-4
|View full text |Cite
|
Sign up to set email alerts
|

High heritability of bone size at the hip and spine in Chinese

Abstract: Bone size, an independent determinant of bone strength, is an important risk factor for osteoporotic fracture. In the present study, we investigated the magnitude of the genetic determination of bone size at the spine and hip and their genetic covariation (if any) in a population of Chinese residing in Shanghai City of P.R. China. The subjects were 50 healthy full-sib pairs of females, 188 mother-daughter pairs, and 128 husbandwife pairs selected from 401 nuclear families. Bone size (centimeters squared) was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Except for cortical volumetric BMD, residual heritabilities of areal and volumetric BMD in our Afro-Caribbean families ranged from 0.55 (for femoral neck) to 0.70 (for radius trabecular BMD). Similar to family studies in other population groups, (13,42) genes accounted for a larger proportion of the total variation than did measured covariates in our Afro-Caribbean families. We do not know why heritability of cortical volumetric BMD at the radius and tibia was considerably lower than that for trabecular volumetric BMD or areal BMD.…”
Section: Discussionsupporting
confidence: 84%
“…Except for cortical volumetric BMD, residual heritabilities of areal and volumetric BMD in our Afro-Caribbean families ranged from 0.55 (for femoral neck) to 0.70 (for radius trabecular BMD). Similar to family studies in other population groups, (13,42) genes accounted for a larger proportion of the total variation than did measured covariates in our Afro-Caribbean families. We do not know why heritability of cortical volumetric BMD at the radius and tibia was considerably lower than that for trabecular volumetric BMD or areal BMD.…”
Section: Discussionsupporting
confidence: 84%
“…Malefemale differences in a variety of indices related to hip geometry and structure have been reported [Beck et al, 1992;Kaptoge et al, 2003], many of which are also related to hip fracture independently of BMD [Gluer et al, 1994;Partanen et al, 2001;Beck et al, 1996;Karlsson et al, 1996]. Genetic influences on some of these measures have been reported [Jian et al, 2004;Liu et al, 2004;Koller et al, 2003], although the sexspecificity of these effects has not yet been investigated.…”
Section: Discussionmentioning
confidence: 96%
“…Liu et al (2004a) reported h 2 estimates of 0.62 for spine bone size and 0.59 for total hip bone size. Other studies reported h 2 estimates of 0.60-0.63 for spine area and 0.45-0.69 for total hip area (Jian et al 2004), and 0.81 for spine BMD and 0.90 for total hip BMD (Liu et al 2004b). The h 2 estimates for trochanter and femoral neck BMD and bone size have not been reported previously.…”
Section: Discussionmentioning
confidence: 97%